Menggugat Ketimpangan dalam Tata Kelola Ekowisata: Perspektif Komunitas Lokal di UNESCO Global Geopark Ciletuh - Adrian, Ilham; Adrian, Rina Hermawati (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
This article examines how power and inequality are reproduced and contested in ecotourism governance from the perspective of local communities in the Ciletuh–Palabuhanratu UNESCO Global Geopark (CPUGG), Indonesia. Using a qualitative ethnographic approach that combines participatory observation, indepth interviews, and document analysis, the study explores how local actors experience exclusion in decision-making, benefit distribution, and cultural representation. Drawing on Michel Foucault’s concept of governmentality and Stuart Hall’s theory of representation, the research demonstrates that governance operates not only through formal institutions but also through symbolic and everyday practices that shape inclusion and control. Furthermore, by integrating Arturo Escobar’s post-development critique and James C. Scott’s notion of everyday resistance, the analysis reveals how communities mobilize social capital, kinship, and cultural values to negotiate power and reclaim agency within global tourism structures. The findings show that while state authorities and private investors dominate ecotourism planning and benefits, local communities respond through micro-level self-organization, such as cooperative homestay networks, boat-sharing systems, and cultural performance groups, that embody governmentality from below. This study contributes to the political anthropology of tourism by showing how everyday resistance redefines local agency in the context of global ecotourism governance. It advances an understanding of ecotourism governance not merely as policy management but as a field of struggle over meaning, identity, and justice, highlighting the need for inclusive deliberation, recognition of local knowledge, and equitable distribution of benefits in sustainable tourism governance.